Migration und Lebenszufriedenheit Eine theoriegeleitete empirische Analyse - Kämpfer, Sylvia (Verlag Barbara Budrich, 2014)
The author examines the life satisfaction of various immigrant groups in Germany. On the one hand, she describes the life satisfaction of immigrants in comparison to the life satisfaction of West Germans. On the other hand, she explains the multidimensional life satisfaction in general and the life satisfaction of migrants of different origins in particular.